When a Peasant Can Only Grieve or Rejoice: Thomas and Znaniecki’s Approach to Emotions - Dowgiałło, Bogna (Stan Rzeczy, 2018)
The present article represents a new attempt to read the first two volumes of The Polish Peasant in Europe and America from the perspective of the sociology of emotions. Reconstructing Thomas and Znaniecki’s approach to emotions entails defining the place of emotions (as emotional habits, feelings, and sentiments) in a theoretical framework of values and attitudes and presenting how Thomas and Znaniecki took affectivity into account at the analytical level. The authors’ approach seems to correspond to the contemporary understanding of emotions, which avoids a separation between the individual and the social, the emotive and the cognitive.